(untitled) (ЕтноАнтропоЗум, 2002)
Epiphany, Bogojavlenie or Vodici (in Macedonian) celebrated on 19/6 January, the day of Jesus’ Baptism, as well as the following day which is dedicated to St. John the Baptist, are one of the most important holidays in the orthodox and the traditional calendar of Macedonians. This text examines two key elements of these holidays - the Baptism and the figure of the Baptist, examined through a few interconnected, but still not identical levels: the theological, the artistic (focusing upon the differences in the representation and understanding of the above mentioned elements in the Western and the Eastern - Byzantine art, using examples from Macedonia) and the level of traditional, above all, Macedonian culture.